The Influence of Beauty Vloggers, Brand Image, and Product Quality on Lipstick Purchase Decision: A Case of Kathmandu Valley - Magar, Anjila Budha (Nepalese Journal of Management, 2025)
This study examines the influence of beauty vloggers, brand image, and product quality on lipstick purchase decision: A case of Kathmandu valley. Purchase decision is the dependable variables. The independent variables are brand image, beauty vloggers influence, price, promotion, and perceived quality. The study is based on primary data with 123 respondents. To achieve the purpose of the study, structured questionnaire is prepared. The correlation coefficients and regression models are estimated to test the significance and the influence of beauty vloggers,brand image, and product quality on lipstick purchase decision in Kathmandu valley. The study showed that brand image is positively correlated to purchase decision. It means that better the brand image higher will be the purchase decision. Likewise, beauty vloggers influence is positively correlated to purchase decision. It implies that the more trust on beauty vloggers influence results to increases in the purchase decision. Similarly, product quality has a positive relationship with purchase decision indicating that increase in the product quality aspect leads to increase in purchase decision. Furthermore, promotion has a positive relationship with purchase decision. It implies that better promotion leads to increase in purchase decision. Likewise, perceived quality is positively correlated to the purchase decision indicating that higher the perceived quality, higher will be the purchase decision.